2016
DOI: 10.1021/acsami.6b00305
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Co3O4/SnO2 Core–Shell Nanospheres as Real-Time Rapid-Response Sensors for Ammonia Gas

Abstract: Novel hybrid Co3O4/SnO2 core-shell nanospheres have been effectively realized by a one-step hydrothermal, template-free preparation method. Our strategy involves a simple fabrication scheme that entails the coating of natural cross-link agents followed by electrostatic interaction between the positive charges of Sn and Co ions and the negative charge of glutamic acid. The core-shell architecture enables novel flexibility of gas sensor surfaces compared to commonly used bulk materials. The highly efficient char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(47 citation statements)
references
References 33 publications
1
46
0
Order By: Relevance
“…The typical n-type semiconductor ZnO is considered to be an extremely beneficial gas-sensing material by reason of good chemical stability, non-toxicity, high surface-to-volume ratio, suitable doping, and low cost [9,10,11]. It is worth noting that the fabrication of heterostructure composite sensors can enhance gas-sensing performances and significantly improve the low sensitivity and poor selectivity of pure ZnO materials [12,13,14]. Kim et al [15] reported the CuO-ZnO heterostructure nanorods sensor to enhance H 2 S gas response and repeatability over pure ZnO.…”
Section: Introductionmentioning
confidence: 99%
“…The typical n-type semiconductor ZnO is considered to be an extremely beneficial gas-sensing material by reason of good chemical stability, non-toxicity, high surface-to-volume ratio, suitable doping, and low cost [9,10,11]. It is worth noting that the fabrication of heterostructure composite sensors can enhance gas-sensing performances and significantly improve the low sensitivity and poor selectivity of pure ZnO materials [12,13,14]. Kim et al [15] reported the CuO-ZnO heterostructure nanorods sensor to enhance H 2 S gas response and repeatability over pure ZnO.…”
Section: Introductionmentioning
confidence: 99%
“…9). 6,26 In this work, the optimal operating temperature of MLTPS was 130 C. At low operating temperatures (<200 C), 34,45 the chemisorbed oxygen ion process can be expressed as follows: 26…”
Section: Sensing Mechanismmentioning
confidence: 99%
“…The SnO 2 /SiO 2 heterojunctions were synthesised via a facile method of a magnetron sputtering process and exhibited promising H 2 sensing performance at room temperature [51]. Hybrid Co 3 O 4 /SnO 2 core-shell nanospheres prepared with a onestep hydrothermal method demonstrated a measured response of 13.6 to 100 ppm NH 3 at 200 • C, a value two times higher than that of the solid nanospheres [52]. CeO 2 -decorated ZnO nanosheets were prepared by a hydrothermal process in combination with the wet impregnation method, exhibited an enhanced sensor response of 90 to 100 ppm ethanol at 310 • C [53].…”
Section: Gas Sensors Based On N-n Junctionsmentioning
confidence: 99%